PENGADAAN TANAH UNTUK SIAPA, PENIADAAN TANAH DARI SIAPA: PENGADAAN TANAH, ALOKASI TANAH, DAN KONFLIK AGRARIA - Tohari, Amien (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
The paper is aimed at discussing whether the policy of land acquisition can become a scheme of agrarian conflict solution. Seen from the land acquisition as a practice of conflict solution, the paper is directly focused on conflict of agrarian context, that is whether the land acquisition can be an alternative solution scheme which can be used to solve the agrarian conflict. The paper wants to state that: first, the land acquisition is not intended as a scheme to solve the problem, second, the policy is a double blade knife that is acquisition and at the same time it is also the abolishment, third, the policy of land acquisition is intended to hold the infrastructural building, fourth,- through the agrarian conflict at Musi Banyuasin, the paper showed that the absence of land acquisition policy or land allocation for the society resulted unresolvable conflict. Keywords: land acquisition policy, conflict, unresolvable